1986
DOI: 10.1039/p29860001525
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of pinane derivatives. Part 9. 8,8-Dimethyltricyclo[5.1.1.02,5]nonan-2β-ol, a tricyclic pinane derivative

Abstract: Acetolysis of the toluene-p-sulphonate ester of 2-(2-hydroxyethyl) -6,6-dimethylbicyclo[3.1.13 hept-2-ene (nopol) (1; R = OH) gave a good yield of the acetate of the previously unknown tricyclic pinane derivative 8,8-dimethyltricyclo[5.1.1 .02*5] nonan-2P-01 (4a). This molecule has a bridgehead hydroxy group, and so is remarkably stable to acids, despite being highly strained from having two cyclobutane rings. However, the hydroxy group is adjacent to the new cyclobutane ring, so that (4a) is readily oxidised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Aldehyde (+)-4o, finally, was obtained from (-)-20 [44] (59% yield) and represents, with (+)-4f (and (+)-4c), a potential homologue of (+)-4b, after appropriate transformations. Epoxidation of iodide (-)-7a resulted in the formation of a mixture of (-)-2g (22%), (-)-3g (20%), and (+)-12 (44%, Scheme 3 ) [45]. Finally, aldehyde (+)-13 [46], with an exocyclic C=C bond, was obtained selectively in 71 YO yield from (+)-4f by a thermal retuo-Prins reaction (Scheme 4 ) .…”
mentioning
confidence: 99%
“…Aldehyde (+)-4o, finally, was obtained from (-)-20 [44] (59% yield) and represents, with (+)-4f (and (+)-4c), a potential homologue of (+)-4b, after appropriate transformations. Epoxidation of iodide (-)-7a resulted in the formation of a mixture of (-)-2g (22%), (-)-3g (20%), and (+)-12 (44%, Scheme 3 ) [45]. Finally, aldehyde (+)-13 [46], with an exocyclic C=C bond, was obtained selectively in 71 YO yield from (+)-4f by a thermal retuo-Prins reaction (Scheme 4 ) .…”
mentioning
confidence: 99%
“…The other product observed during acetolysis of nopyl toluene-p-sulfonate is 1-ethyl-4-(2-propyl)benzene (26), probably arising as a result of breaking the gem-dimethyl bridge. 1 This contrasts with the observation 20,21 that the parent hydrocarbon of 2 (brendane, 27) can be converted easily into noradamantane 28. Calculation of the enthalpies of formation of these molecules confirms that such rearrangement is energetically favourable.…”
Section: Resultsmentioning
confidence: 78%
“…It was converted into its toluene-p-sulfonate ester by conventional methods 1 and was subjected to acetolysis in acetic acid as described earlier. 1 The product was distilled to yield fortesyl unlabelled fortesol was absent in this labelled material. The 1 H NMR spectrum showed that a multiplet at δ 1.88 corresponding to the equatorial hydrogen on C-4 was absent.…”
Section: Preparation Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conformations of a number of halohydrins derived from (+)-car-3-ene (231) have been studied using IR spectroscopy.255 Diels-Alder reaction of isoprene with (a-1 -tributylstannylbut-1-en-3-one yields the adduct (234), which can be converted into (-t)-car-3-ene (231) on its treatment with MeLi followed by SOC12-pyridine.248 (+)-Car-2-ene (233) has been used as starting material in a synthesis of the cembranoid ( + ) -~a s b e n e , ~~~ and (-))-trans-caran-2-one (235) can be converted into the useful guiane synthon (+ ) - (236). 134 A reactor for the large-scale homogeneous catalytic autoxidation of (+)-car-3-ene (231) has been described.…”
Section: Thujanesmentioning
confidence: 99%